Education Vouchers : Constitutional Issues and Cases. (U.S. Congressional Research., 2002)
Examines constitutional standards the Supreme Court has articulated both for direct public aid to sectarian schools and for indirect aid by way of vouchers. Summarizes recent decisions involving voucher and voucher-related programs by State and lower Federal courts.